2008
DOI: 10.1007/s12010-008-8321-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silica-Derived Nano-Supporters on Cellobiase After Immobilization

Abstract: Core shell magnetite nanoparticle (CSMN) was successfully synthesized with diameter around 125 nm according to the determination with scanning electronic microscopy. SBA-15 with diameter around 31 nm was synthesized in our previous work as another supporter for immobilized degradation enzymes. The aim of this study was to investigate the influence of silica-derived nano-supporters on cellobiase after immobilization. With covalent method, glutaraldehyde was introduced to immobilize cellobiase. The immobilized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Calsavara et al (2001) reported that t ½ of free and immobilized cellobiase at 65 ºC were 2.1 and 21.3 h, respectively. This is probably due to the formation of multiple covalent bonds between β-glucosidase and the support that reduce conformational flexibility and thermal vibration, thus preventing the immobilized protein from unfolding and denaturing (Mateo et al, 2000;Wang et al, 2009;Figueira et al, 2011). The deactivation rate constant at 65 ºC for the immobilized β-glucosidase is 9.5x10 -3 / min, which is lower than that of the free form (12.53x10 -3 / min).…”
Section: Thermal Stabilitymentioning
confidence: 97%
“…Calsavara et al (2001) reported that t ½ of free and immobilized cellobiase at 65 ºC were 2.1 and 21.3 h, respectively. This is probably due to the formation of multiple covalent bonds between β-glucosidase and the support that reduce conformational flexibility and thermal vibration, thus preventing the immobilized protein from unfolding and denaturing (Mateo et al, 2000;Wang et al, 2009;Figueira et al, 2011). The deactivation rate constant at 65 ºC for the immobilized β-glucosidase is 9.5x10 -3 / min, which is lower than that of the free form (12.53x10 -3 / min).…”
Section: Thermal Stabilitymentioning
confidence: 97%
“…ey have been used extensively for various applications including photothermal therapy [19], photodynamic therapy [20,21], magnetic resonance imaging [22], peptide delivery [23], and gene delivery [24,25]. SiNPs are "tunable" because they are easily modi�ed with functional groups like -COOH and -NH 2 , which allows conjugation with a target moiety for targeted delivery and, therefore, promotes better therapies as well as prognosis [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However in other reports, immobilization of b-glucosidase on SiO 2 nanoparticles caused an increase in both the K m (2.5 mM for free and 3.8 mM for immobilized) and V max (3028 U/ mg protein to 3347 U/mg protein) of the enzyme (Singh et al 2011). The K m and V max values were 27.1 mM and 3.41 mmol/mg/min for free glucose oxidase while 14.6 mM and 0.116 mmol/mg/min for glucose oxidase immobilized on aminated-CoFe 2 O 4 /SiO 2 magnetic nanoparticles (Wang et al 2009). Similar results were found by Georgelin et al (2010) with increase K m (from 7.6 mM to 8.6 mM) and decreased k cat (from 69 to 34 s -1 ) after immobilization of b-glucosidase on functionalized cFe 2 O 3 @ SiO 2 core-shell magnetic nanoparticles.…”
Section: Kinetic Parameters Of Free and Immobilized B-glucosidasementioning
confidence: 96%